Gender Budgeting and its Outcome on Women Labour Force Participation in Unorganized sector - Mehrotra, Manisha A.; Pandey, Prashant Kumar (Archives of Business Research, 2022)
Unorganized sector always plays a vital role in terms of providing employment opportunities to a large segment of the workforce in India. Near about 92% of the total employment in the Indian economy during the period 1999-2000 was accounted for by the unorganized/informal sector (NSSO 55th Round 1999-2000). In most states the share of informal workers is approximately the same as the national average. Female work participation has always been low at 26.97% compared to 52% of men (World Bank Report, March 2018). The problem is that women have always been at work; only the definitions of work and work plan have never been defined or realistic to include their contribution to the economy and the society. In order to deal with gender disparity and bring efficacy in women labour force participation, Gender Budgeting was started in India in 2004. However, the outcomes show that their condition has improved in formal sector but in informal sector the working conditions has not much improved. The aim of this paper is to evaluate some of the new initiatives taken by Government of India in Public Economics in reference to Gender budgeting. It relates to government expenditure in welfare measures for the upliftment of women labour force participation in organized sector. The researchers tried to find out the outcomes of gender budgeting by critically evaluating the changing pattern of Indian working women in the unorganized sector and find out the condition of health, safety and well- being of working women in unorganized sector of India.